Paenibacillus lautus, an opportunistic bacterial pathogen, isolated from Ixodes granulatus Supino (Acari: Ixodidae) collected from a Müller’s giant Sunda rat (Sundamys muelleri) - Loong, Shih Keng; Ishak, Siti Nabilah; Lim, Fang Shiang; Khoo, Jing Jing; Tan, Sing Ngoh; Freddy-Jalin, Eunice Jalin; Mohd-Taib, Farah Shafawati; AbuBakar, Sazaly (Systematic and Applied Acarology Society, 2018)
Wild rodents are carriers of ectoparasites such as ticks that are vectors of infectious diseases with human and veterinary significances. Due to their close association with human dwellings, synanthropic wild rodents may aid the spread and transmission of tick-borne pathogens. In light of this, an effort was initiated to study the cultivable bacteria within ticks collected from wild rodents trapped in Sungai Congkak Recreational Forest, Selangor. Ticks collected from four different rodent species; Sundamys muelleri, Maxomys whiteheadi, Maxomys rajah and Rattus rattus, were sterilely homogenized and cultured. One unique bacterial isolate originating from an engorged adult female Ixodes granulatus Supino collected off a Sundamys muelleri rat was identified as Paenibacilus lautus via 16S rDNA, ctpA sequencing and biochemical tests. Antimicrobial susceptibility testing revealed that the P. lautus isolate was resistant to ampicillin, penicillin, clindamycin, chloramphenicol, rifampicin and trimethoprim-sulfamethoxazole, mirroring the antimicrobial susceptibility profiles of clinical strains. Recovery of this opportunistic bacterial pathogen from the tick suggests that it may be transmitted to humans or other hosts through tick bites and cause disease once it enters the bloodstream. Therefore, it is important to remain vigilant due to its pathogenic potential and improve our waste disposal practices to avoid attracting rodents.